Enhancement of mechanical behavior of FRP composites modified by silica nanoparticles. (30th November 2020) - Su, Chang; Wang, Xin; Ding, Lining; Wu, Zhishen
Highlights: Silica nanoparticles allow the resin to have better toughness and mechanical behavior. Mechanism of mechanical enhancement is revealed by SEM analysis of fracture surfaces. The breaking stress enhancement of silica nanoparticle-modified impregnated roving. Models of the relationship between tensile strength of FRP and nanoparticle contents. Abstract: To enhance the mechanical behavior of fiber-reinforced polymers (FRPs), the mechanical properties of epoxy and vinyl ester resin and two types of FRP modified by silica nanoparticles at 1, 2, 3, and 4 wt% are investigated herein. Fracture toughness tests of the casting resin were conducted, and scanning electron microscopy (SEM) was performed to identify the fracture surface and toughening mechanism. Damage mechanisms of resin with nanoparticles were analyzed and differences owing to varying nanoparticle contents were identified. Impregnated fiber roving with modified resin was studied for enhancements in tensile strength and stiffness. Results showed that the addition of silica nanoparticles to the epoxy/vinyl ester resin improved the mechanical properties, which reached the maximum at the nanoparticle content of 3 wt%. The tensile, flexural, and impact strengths of the epoxy resin increased by 26%, 6%, and 49%, respectively, compared with the control epoxy resin. Furthermore, the corresponding enhancements of the vinyl ester resin are 17%, 17%, and 94%. At the same particle content, the fracture toughness of the epoxy and vinyl ester resins are increased by 12% and 20%, respectively. SEM of the fracture surface reveals a relatively rough surface with tortuous cracks, thereby resulting in a higher fracture toughness of the modified resin. The tensile strength of the impregnated basalt fiber roving made of the modified vinyl ester resin increased, and results show an 18% increase at the particle content of 3 wt%. Meanwhile, the adoption of epoxy resin with silica nanoparticles resulted in the basalt and impregnated carbon fiber roving achieving higher tensile strength and stiffness compared with those without nanoparticles.